A Fun Palace: Cybernetics, feed(loops)back and mixed reality - Riecke, Bernhard E.; Pennefather, Patrick (Acting Cybernetically: 2019 Conference of the American Society for Cybernetics, 2019)
Riecke and Pennefather will present on the process of reimagining a version of the Fun Palace, realized as a mixed reality installation. This will be combined with detailing the types of persistent feedback loops that occurred (and are still occurring) during the research creation process, and those designed to manifest within the mixed reality Fun Palace installation.
Keywords: NSERC DG 2026; Riecke; Riecke_2019; bernhard-riecke; conferenceTalksWithoutPaper; keynoteTalk; patrick-pennefather; talkWithoutPaper